Fe3O4-Silicone Mixture as Flexible Actuator - Song, Kahye; Cha, Youngsu (MDPI, 2018)
In this study, we introduce Fe3O4-silicone flexible composite actuators fabricated by combining silicone and iron oxide particles. The actuators exploit the flexibility of silicone and the electric conductivity of iron oxide particles. These actuators are activated by electrostatic force using the properties of the metal particles. Herein, we investigate the characteristic changes in actuation performance by increasing the concentration of iron oxide from 1% to 20%. The developed flexible actuators exhibit a resonant frequency near 3 Hz and their actuation amplitudes increase with increasing input voltage. We found that the actuator can move well at metal particle concentrations >2.5%. We also studied the changes in actuation behavior, depending on the portion of the Fe3O4-silicone in the length. Overall, we experimentally analyzed the characteristics of the newly proposed metal particle-silicone composite actuators.
Keywords: DIELECTRIC ELASTOMERS; SOFT